The cyl Genes Reveal the Biosynthetic and Evolutionary Origins of the Group B Streptococcus Hemolytic Lipid, Granadaene - Armistead, Blair; Whidbey, Christopher; Iyer, Lakshminarayan M.; Herrero-Foncubierta, Pilar; Quach, Phoenicia; Haidour, Ali; Aravind, L.; Cuerva, Juan Manuel; Jaspan, Heather B.; Rajagopal, Lakshmi (Frontiers in Microbiology, 2020)
Group B Streptococcus (GBS) is a β-hemolytic, Gram-positive bacterium that commonly colonizes the female lower genital tract and is associated with fetal injury, preterm birth, spontaneous abortion, and neonatal infections. A major factor promoting GBS virulence is the β-hemolysin/cytolysin, which is cytotoxic to several host cells. We recently showed that the ornithine rhamnolipid pigment, Granadaene, produced by the gene products of the cyl operon, is hemolytic. Here, we demonstrate that heterologous expression of the GBS cyl operon conferred hemolysis, pigmentation, and cytoxicity to Lactococcus lactis, a model non-hemolytic Gram-positive bacterium. Similarly, pigment purified from L. lactis is hemolytic, cytolytic, and identical in structure to Granadaene extracted from GBS, indicating the cyl operon is sufficient for Granadaene production in a heterologous host. Using a systematic survey of phyletic patterns and contextual associations of the cyl genes, we identify homologues of the cyl operon in physiologically diverse Gram-positive bacteria and propose undescribed functions of cyl gene products. Together, these findings bring greater understanding to the biosynthesis and evolutionary foundations of a key GBS virulence factor and suggest that such potentially toxic lipids may be encoded by other bacteria.